PENGUJIAN MATERIIL SURAT KEPUTUSAN DIREKSI PT. BANK RAKYAT INDONESIA (PERSERO) TENTANG PEMUTUSAN HUBUNGAN KERJA (Studi Kasus Putusan Mahkamah Agung Nomor 08 P/HUM/2019) - Bahri Pasaribu (Jurnal Hukum dan Kemasyarakatan Al-Hikmah, 2020)
AbstractTesting the law is a must for assessing whether an assessment-invitation regulation is in accordance with or contradictory to a higher degree of regulation, as well as a certain regulation relating to certain regulations.The problems in this paper are: material testing of a decision of a state-owned enterprise in Indonesian laws and regulations, the trial process of a material test of a state-owned enterprise decision letter in the Decision of the Supreme Court of the Republic of Indonesia Number 08 P / HUM / 2019, consideration of judges in material test of PT. Bank Rakyat Indonesia (Persero) in the decision of the Supreme Court Number 08 P / HUM / 2019This research is descriptive in nature using normative juridical. "Normative juridical decisions are decisions on legal science with a focus on secondary data, consisting of primary, secondary and tertiary legal material", and to complete the data carried out by collecting relevant materials and conducting library studies from which data will then be accessed by juridists.It was concluded that the material examination of a decision of a state-owned business entity in the laws and regulations in Indonesia, namely the Testing of Legislation under the law against the law, was carried out by the Supreme Court in exercising judicial power as an attribute authority, under the law. The trial process of the material test of state-owned enterprise decision letter in the Supreme Court Decree No. 08 P / HUM / 2019 namely the HUM application can be submitted in two ways, namely: submitted directly to the Supreme Court, registered with the Registrar of the Supreme Court and recorded in a separate register book different from other Supreme Court hearings, or can also be submitted through the District Court / Local Administrative Court also follow the procedure and procedure for the trial of the local court. Judge's consideration in the material test of Bank Rakyat Indonesia's board of directors' decision letter in the Supreme Court's decision No. 08 P / HUM / 2019, the provision so that the object of the application in this case can be tested by the Supreme Court, the object of the application must be statutory regulations under the law. Object of application for Decree of the Directors of BRI. The a quo petition case does not meet the requirements as a statutory regulation, so that the Supreme Court is not authorized to examine the object of the application, therefore the petition for the petition of the Petitioners must be declared inadmissible. Keywords         :           Material Test Rights, Directors, Banks, Termination of Employment.     Abstrak Pengujian Undang-Undang merupakan suatu wewenang untuk menilai apakah suatu peraturan perundang-undangan isinya sesuai atau bertentangan dengan peraturan yang lebih tinggi derajatnya, serta apakah suatu kekuasaan tertentu berhak mengeluarkan suatu peraturan tertentu.Permasalahan dalam penulisan ini adalah : pengujian materiil terhadap suatu keputusan badan usaha milik negara dalam peraturan perundang-undangan di Indonesia, proses persidangan uji materiil surat keputusan badan usaha milik negara dalam Putusan Mahkamah Agung Republik Indonesia Nomor 08 P/HUM/2019, pertimbangan hakim dalam uji materiil surat keputusan direksi PT. Bank Rakyat Indonesia (Persero) dalam putusan Mahkamah Agung Nomor 08 P/HUM/2019Penelitian ini bersifat deskriptif dengan pendekatan yuridis normatif. “Pendekatan yuridis normatif yaitu menekankan pada ilmu hukum dengan menitik beratkan pada data sekunder, yang berupa bahan hukum primer, sekunder, dan tertier”, dan untuk melengkapi data dilakukan dengan mengumpulkan bahan-bahan yang relevan dan melakukan studi pustaka yang selanjutnya data akan dianalisis secara yuridis.Disimpulkan bahwa Pengujian materiil suatu keputusan badan usaha milik negara dalam peraturan perundang-undangan di Indonesia yakni Pengujian Peraturan Perundang-Undangan dibawah undang-undang terhadap undang-undang, dilakukan MA dalam menjalankan kekuasaan kehakiman sebagai kewenangan atributif, MA berwenang melakukan Pengujian Peraturan Perundang-Undangan di bawah Undang-Undang. Proses persidangan uji materiil surat keputusan badan usaha milik negara dalam Putusan MA RI Nomor 08 P/HUM/2019 yakni permohonan HUM dapat diajukan dengan dua cara yaitu: diajukan langsung ke MA, dengan didaftarkan ke kepaniteraan MA dan dibukukan dalam buku register tersendiri yang berbeda dari sidang MA lainnya, atau bisa juga diajukan Melalui Pengadilan Negeri/PTUN Setempat juga mengikuti prosedur dan tata cara persidangan dari perdilan setempat. Pertimbangan hakim dalam uji materiil surat keputusan direksi Bank Rakyat Indonesia dalam putusan Mahkamah Agung No 08 P/HUM/2019, ketentuan agar objek permohonan dalam perkara ini dapat diuji oleh MA, objek permohonan harus peraturan perundang-undangan di bawah undang-undang. Objek permohonan Surat Keputusan Direksi BRI. Perkara permohonan a quo tidak memenuhi syarat sebagai sebuah peraturan perundang-undangan, sehingga MA tidak berwenang menguji objek permohonan, karenanya permohonan hak uji materiil Para Pemohon harus dinyatakan tidak dapat diterima.Kata Kunci        :           Hak Uji Materiil, Direksi, Bank, Pemutusan Hubungan Kerja.